Just world order dream or reality - Farooqui, Jamil (Radiance Views Weekly, 2012)
Humans have been struggling from the very dawn of civilization to establish an ‘order’ wherein they can fulfil their aspirations, and live with their brethren in peace and harmony with dignity and honour. They have made serious and rigorous efforts in this direction but it still remained only a dream. They thought it could be possible if they created sophisticated means of livelihood, developed adequate and advanced technology and mechanical devices to satisfy their urges. As a matter of fact, they developed knowledge, particularly scientific knowledge (which is believed to be capable of curing all of their ailments), discovered the treasures of nature, invented great machines and tools, provided humanity with utmost material comfort and made human life more and more comfortable. They also developed different socio-economic and political systems as well as advanced methods of governance, which may ensure individual freedom, safety of their lives and property as well as their genuine right of existence. In spite of all these efforts and developments, the human world remains unsafe and human life is more fragile than we ever imagined. Our scientific discoveries and sophisticated technologies made the environment highly polluted to the extent that it is difficult to taste the fresh air. Our socio-political systems have failed to protect individual freedom, safeguard human dignity, and guarantee the human right of existence to every individual irrespective of caste, creed and colour. Our economic system failed to provide bread and butter to millions of our brethren who are leading an animalistic life......